Ameliorative effect of sansoninto on sleep disturbance and spatial memory impairment in an Alzheimer's disease rat model. Issue 1 (7th March 2017) - Moriyama, Hiroshi; Watanabe, Takuya; Takasaki, Kotaro; Nagao, Masaki; Kubota, Kaori; Katsurabayashi, Shutaro; Egashira, Nobuaki; Iwasaki, Katsunori
ABSTRACT: Aim: Alzheimer's disease (AD) is associated with a high incidence of sleep disturbance, and several studies have reported that sansoninto (SNT), a Kampo medicine, ameliorates sleep disturbance. The effects of SNT on sleep disturbance and spatial memory impairment, however, have not been investigated in animal models of AD, therefore the aim of the current study was to carry out these investigations using a rat AD model. Methods: Combined cerebral ischemia and intracerebroventricular injections of aggregated beta‐amyloid were used to induce a rat model of AD. The quantity and quality of sleep in these rats were determined on electroencephalography and electromyography. Spatial memory impairment was examined using the water maze task. Triazolam, a hypnotic, and donepezil, approved for treating AD, were used as positive controls. Results: Compared with sham‐operated rats, the AD model rats had decreased total non‐rapid eye movement sleep time, more frequent nocturnal awakening in the light phase, and poorer quality of non‐rapid eye movement and rapid eye movement sleep on electroencephalography and electromyography. The AD rats also took longer than sham‐operated rats to pass the platform area in the water maze retention test. Oral SNT 1000 mg/kg improved those impairments. Conclusion: SNT ameliorated not only the abnormal non‐rapid eye movement and rapid eye movement sleep structure but also the spatial memory impairment observed in a rat model of AD.